AUDIT MANAJEMEN SUMBER DAYA MANUSIA DAN KINERJA KARYAWAN: BUKTI EMPIRIS DARI PT POS INDONESIA (PERSERO) KANTOR CABANG UTAMA BANDUNG - Fitriani; Audita Setiawan; Medianto Suryo; Fahmi Damarjati (Universitas Sangga Buana, 2026)
This study aims to analyze the effect of Human Resource Management Audit on employee performance at PT Pos Indonesia (Persero) Bandung Main Branch Office. A quantitative approach with a survey method was employed involving 35 employees selected using a saturated sampling technique. Primary data were collected through questionnaires and analyzed using simple linear regression analysis. The results indicate that Human Resource Management Audit has a positive and significant effect on employee performance. These findings suggest that effective implementation of HR management audits enhances employee performance through the evaluation and improvement of human resource management functions. This study provides empirical evidence that Human Resource Management Audit serves as a strategic mechanism for improving the effectiveness of human resource management in a state-owned logistics service company.